Unlocking the potential of ‘Egusi’ melon (Colocynthis citrullus L.) as a crop for biotechnological improvement - Anwar, Aliya Fathima; Chukwurah, Peter Nkachukwu; Amombo, Erick; Mouhib, Salma; Ntui, Valentine Otang (Frontiers in Plant Science, 2025)
‘Egusi’ melon (Colocynthis citrullus L.) plays a critical role in food security and potential biofuel production in West Africa. Its seeds are valued for both their nutritional and potential industrial applications, especially in biodiesel production. However, the crop faces significant challenges, including the impacts of climate change, water scarcity, declining arable land, and increased pressure from pests and diseases. These challenges threaten the stability of ‘Egusi’ production and may hinder its ability to meet future demand. To address these issues, there is a growing need to complement conventional breeding methods with biotechnological approaches. Molecular approaches; including genomics, transcriptomics, proteomics, and metabolomics; have been utilized for the improvement of several cucurbit species. However, information on molecular breeding of ‘Egusi’ is very limited. The current review focuses on ‘Egusi’ melon, its biology, uses, and factors affecting its improvement, and highlights critical knowledge gaps in the molecular breeding of ‘Egusi’. The review also examines the potential of omics technologies and outlines the importance of genetic transformation and genome editing methods such as CRISPR that could drive the development of more resilient and high-yielding ‘Egusi’varieties that will contribute to sustainability and profitability of ‘Egusi’ farming.